PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI DI KOTA PROVINSI JAWA TIMUR - Mareta Dea Alifianti; Nurul Lathifah (Jurnal Ekonomi Dan Bisnis, 2025)
This study aims to analyze the influence of local revenue and balancing funds on economic growth in cities in East Java, both partially and simultaneously. The data used are sourced from BPS, the Directorate General of Fiscal Balance, and the Regional Budget (APBD) realization report. The study uses an associative quantitative approach and is analyzed using multiple linear regression through SPSS 26. The results show that simultaneously local revenue and balancing funds have a significant effect on economic growth. Partially, local revenue does not have a significant effect on economic growth, while balancing funds have a positive effect on economic growth.